2016
DOI: 10.1140/epjd/e2016-70124-7
|View full text |Cite
|
Sign up to set email alerts
|

Higher lying resonances in low-energy electron scattering with carbon monoxide*

Abstract: Abstract. R-matrix calculations on electron collisions with CO are reported whose aim is to identify any higher-lying resonances above the well-reported and lowest 2 Π resonance at about 1.6 eV. Extensive tests with respect to basis sets, target models and scattering models are performed. The final results are reported for the larger cc-pVTZ basis set using a 50 state close-coupling (CC) calculation. The BreitWigner eigenphase sum and the time-delay methods are used to detect and fit any resonances. Both these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 92 publications
(146 reference statements)
0
11
0
Order By: Relevance
“…But, in the current studies we observed presence of the two small forward peaks ( Figure 3) for the ions created due to process I and concluded that the coherent interference is not present. In a recent R-matrix calculation Dora et al [13] observed the presence of only a single Σ resonant state around the studied energy range. Furthermore, in recent momentum imaging studies Gope et al [8] also observed the involvement of Σ and Π TNI states and absence of coherent interference.…”
Section: Resultsmentioning
confidence: 92%
“…But, in the current studies we observed presence of the two small forward peaks ( Figure 3) for the ions created due to process I and concluded that the coherent interference is not present. In a recent R-matrix calculation Dora et al [13] observed the presence of only a single Σ resonant state around the studied energy range. Furthermore, in recent momentum imaging studies Gope et al [8] also observed the involvement of Σ and Π TNI states and absence of coherent interference.…”
Section: Resultsmentioning
confidence: 92%
“…In our recent attempt [25] to study the higher lying resonances in CO, our best model, close-coupling method with 50 target states represented using a cc-pVTZ basis set, found only one 2 Σ + resonance at 12.9 eV in addition to the lowlying 2 Π at 1.7 eV. In this study, we report on a similar fixed-nuclei calculation but with a much larger cc-pV6Z basis set.…”
Section: Introductionmentioning
confidence: 73%
“…As in the previous paper [25] (hereafter referred as paper-I), here we report on R-matrix calculation at the equilibrium geometry of CO, R eq = 2.1323 a 0 . As mentioned above, we use the UK molecular R-matrix codes (also called UKRmol codes) [26,27,33] for the scattering calculations.…”
Section: Calculation and Resultsmentioning
confidence: 99%
“…To avoid this region the time-delay calculation is started at some energy above a threshold (default 0.05 eV). We note that this can cause problems with Feshbach resonances which lie very close to their parent target state [22]. Furthermore, for charged systems, when approaching a threshold from below, the width of the Rydberg states converging on the threshold above becomes increasingly narrow.…”
Section: Methodsmentioning
confidence: 91%